Lipid profile and hepatoprotective effects of combined leaf extracts of Azadirachta Indica (Neem) and Peristrophe bicalyculata in Alloxan-induced diabetic rats. - Bob Agboje Ignatius Mgbeje; Nyakmo A Essien; Iwara A Iwara; Godwin Eneji Egbung; Godwin O Igile; Patrick E Ebong (International Journal of Phytomedicine, 2013)
Purpose of the study: This study was designed to investigate the protective efficacy of ethanolic extracts of leaves of Azadirachta indica (AI) and Peristrophe bicalyculata (PB) on the liver of alloxan-induced diabetic albino wistar as well as their effect on serum lipid profile. Main findings: A significant decrease (P<0.05) was observed in HDL, VLDL and triglyceride values while an increase (P<0.05) was observed in LDL and total cholesterol values in the diabetic control (DC) compared with the normal control (NC). Treatment with PB reversed the decrease in HDL levels comparable to the reversal by insulin. All the extracts caused an increase in the value of VLDL compared to DC. The values of LDL decreased significantly (p<0.05) in all the extract-treated rats relative to DC with the combine extracts showing a synergistic decrease. The decrease in TG was significantly (p<0.05) reversed by treatment with all the extracts and insulin while the increase in TC was reversed only by AI. There was an increase in AST and ALT and a decrease in ALP levels in DC, relative to NC. Only the combined extract resulted in a reduction in AST level, relative to DC, comparable to the Insulin value. There was a significant decrease (p<0.05) in ALT level in all treated animals compared to DC. Except for AI, no reversals were observed for ALP levels in all the treatment groups. Summary of findings: The results show that a combination of the two plant extracts will be most appropriate for a total normalization of the diabetes-induced hyperlipidemia and protection of the liver against diabetes-induced injury.